Heat shock proteins purified from autologous tumors using antibody-based affinity chromatography - Kleist, Christian; Randazzo, Marco; Jiga, Janina; Terness, Peter (Cancer vaccines, 2014)
Heat shock proteins (HSP) isolated from autologous tumors have become a promising tool for active-specific anticancer immunotherapy due to their properties as carriers of antigenic peptides on one hand and as immunostimulatory adjuvants on the other. Rapid and efficient isolation of HSP-peptide complexes from a patient's tumor is fundamental for their clinical application. Herein, we describe the purification of the HSP Gp96 and Hsc70/Hsp70 from human autologous tumor sources by one-step antibody-based affinity chromatography. Recombinant anti-Gp96 and anti-Hsp70 single-chain Fv antibodies are covalently coupled to a chromatographic bead resin to obtain highly specific affinity matrices. Chromatographic columns are assembled and then used to simultaneously isolate various HSP from the supernatant of lysates of human tumor samples of different origin in a single chromatographic step.